The Relationship Between Pregnant Women's Compliance in Consuming Iron Tablets and Hemoglobin Levels in the Telaga Dewa Community Health Center Work Area, Bengkulu City, 2024 - Royana, Weni; Tranado , Hengki; Murwati , Murwati (Multidisciplinary Journals, 2025)
Pregnancy is a physiological process that women go through. The pregnancy process begins with conception and ends with childbirth. Prevention of emergency conditions during pregnancy is carried out four times throughout the pregnancy period. This effort is done to observe the development and growth of the fetus and monitor the health of the mother during pregnancy. Mothers will undergo hemodilation or blood tests, which put them at risk of anemia. Method: This study used a cross-sectional approach. There were 42 pregnant women in the Telaga Dewa Community Health Center working area who were selected as research samples using accidental sampling techniques. The research subjects had to meet the predetermined inclusion and exclusion criteria. The research data consisted of primary and secondary data. Data or variables were analyzed using the Chi-square formula. Of the 42 pregnant women, 23 (54.8%) were non-compliant and 19 (42.2%) were compliant. For pregnant women with hemoglobin ≥ 11 gr%, 19 pregnant women (42.2%) took iron tablets, while 23 pregnant women (54.8%) with hemoglobin ≤ 11 gr% took iron tablets. The Chi-Square test yielded a P-value (<0.000) < (0.05), indicating a significant association between pregnant women's compliance in taking iron tablets and hemoglobin levels